2021
DOI: 10.3389/frph.2021.641008
|View full text |Cite
|
Sign up to set email alerts
|

Level and Predictors of Knowledge of Reproductive Rights Among Haramaya University Students, Eastern Ethiopia: A Cross-Sectional Study

Abstract: Background: Globally, two-thirds of pre-mature deaths and one-third of the total disease burden in adults are associated with problems that began in adolescent and youth. Global and national acting educational and health policies, strategies, and programs designed to promote, implement, and improve adolescent and youth sexual and reproductive health services utilization should be responsive, consider the knowledge of reproductive rights and risk factors. This study assessed the level and predictors of knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In this study, the level of knowledge on sexual and reproductive health rights was found to be 52.1% [95% CI (47.32–55.08)]. This finding is consistent with research from Nepal (51.12%) 12 ,52.2% 16 , and 54.5% 15 in Ethiopia. However, it is higher than studies conducted elsewhere in Ethiopia (16.4%), 14 (46.6%), 18 (47.1%) 17 and lower than studies conducted elsewhere in Ethiopia (57.7%), 19 (59.6%) 24 and 60.3% in Ikeja and 62.1% in Ikorodu in Nigeria.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, the level of knowledge on sexual and reproductive health rights was found to be 52.1% [95% CI (47.32–55.08)]. This finding is consistent with research from Nepal (51.12%) 12 ,52.2% 16 , and 54.5% 15 in Ethiopia. However, it is higher than studies conducted elsewhere in Ethiopia (16.4%), 14 (46.6%), 18 (47.1%) 17 and lower than studies conducted elsewhere in Ethiopia (57.7%), 19 (59.6%) 24 and 60.3% in Ikeja and 62.1% in Ikorodu in Nigeria.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a study of Haramaya and Gondar university students found that the presence of reproductive health clubs on campus was significantly associated with optimal knowledge of sexual and reproductive health rights. 16,19 Participants in this study who were members of a reproductive health club were nearly four times more likely to have a good knowledge of sexual and reproductive health rights. Similarly, another study among university students found that https://doi.org/10.2147/AHMT.S394883…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations